Mapping Research Trends In Teaching And Learning Trajectories In Science Learning - Nugraha, Abdurrohman Khotim; Rochman, Chaerul (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
One of the success factors of science learning is determined by the teacher's role in designing learning. A good learning design at least contains three aspects that are mutually sustainable, namely teaching trajectory, learning trajectory, teaching and learning trajectory and authentic assessment. This study aims to map research trends related to teaching and learning trajectory and authentic assessment in science learning. The method used was bibliometric analysis. The sample of articles used amounted to 662 Scopus indexed articles within the last five years. The results of the analysis were then mapped using VOSviewer to show the connections, patterns, correlations and density of research on the topics studied. The mapping results show that not much research has been conducted on teaching and learning trajectories and authentic assessment in science learning over the past five years. Thus, the results of this study are expected to provide a comprehensive picture of the development of research on teaching trajectory, learning trajectory, teaching and learning trajectory and authentic assessment and its implications for educators and or future researchers in designing more effective and innovative science learning designs in the future.